Persepsi Politik Generasi Z di TikTok: Analisis Teori Ekologi Media - Ginting, Geby Enzelica Br; Pribadi, Muhammad Adi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Generation Z uses TikTok as a space to access political information, build perceptions, and express opinions. This study aims to analyze the formation of GenerationZ's political perceptions of TikTok using a qualitative descriptive approach based on media ecology theory. Data collection methods through in-depth interviews, observation, and documentation Research shows that TikTok plays a role in shaping Generation Z's political perceptions through a personalization algorithm that presents content according to user preferences Generation Z actively consumes political content that is creatively packaged in short videos, trending hashtags, and easy-to-understand stories. In addition, TikTok serves as a dynamic space that encourages Generation Z to actively participate in political discussions through interactive features such as duets, remixes, and comments. This process provides Generation Z with a deeper and more thoughtful understanding of political issues. This research provides new insights into TikTok's role in shaping Generation Z's political experiences, particularly in the context of interactions between users, content, and digital technologies. Generasi Z menggunakan TikTok sebagai ruang untuk mengakses informasi politik, membangun persepsi, dan mengekspresikan pendapat. Penelitian ini bertujuan untuk menganalisis pembentukan persepsi politik Generasi Z terhadap TikTok dengan menggunakan pendekatan deskriptif kualitatif berdasarkan teori ekologi media. Metode pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi. Penelitian menunjukkan bahwa TikTok berperan dalam membentuk persepsi politik Generasi Z melalui algoritma personalisasi yang menyajikan konten sesuai preferensi pengguna Generasi Z aktif mengonsumsi konten politik yang dikemas secara kreatif dalam video pendek, hashtag yang sedang tren, dan cerita yang mudah dipahami. Selain itu, TikTok berfungsi sebagai ruang dinamis yang mendorong Generasi Z untuk berpartisipasi aktif dalam diskusi politik melalui fitur interaktif seperti duet, remix, dan komentar. Proses ini memberikan Generasi Z pemahaman yang lebih dalam dan bijaksana mengenai isu-isu politik. Penelitian ini memberikan wawasan baru mengenai peran TikTok dalam membentuk pengalaman politik Generasi Z, khususnya dalam konteks interaksi antara pengguna, konten, dan teknologi digital.